Assessment of her2 expression status, tumour budding and poorly differentiated clusters in colorectal cancer - Firooz, Haroon
In Malaysia, colorectal cancer (CRC) is the second most common tumour. Tumour budding (TB) and poorly differentiated clusters (PDC) have been shown to be independent prognostic factors in CRC, that may allow for stratification of patients into more meaningful risk categories than those defined by TNM staging. However, these parameters are not routinely incorporated as part of the histopathological assessment. The role of Human Epidermal Growth Factor Receptor 2 (HER2) as a prognostic biomarker in CRC remains uncertain. Negative prognostic impact of HER2 expression has been proposed with a trend towards worse overall survival. Therefore, we aimed to evaluate the TB, PDC and HER2 expression status in our CRC cases and assess their associations with the established prognostic clinicopathological parameters including lymphovascular invasion, lymph node metastasis, tumour grade and tumour stage (pTNM). For evaluation of TB and PDC, hematoxylin and eosin-stained slides prepared from tissue blocks of 129 CRC cases diagnosed from 1st January 2017 to 31st December 2018, in Hospital Tengku Ampuan Afzan (HTAA) and Sultan Ahmad Shah Medical Centre @ IIUM, Kuantan Pahang. PDC, and TB according to the International Tumour Budding Consensus Conference (ITBCC) criteria were scored. For HER2 expression, IHC and FISH analysis were utilized, following HERACLES diagnostic criteria. Results: For TB, of the 129 cases studied, 63 (48.8%), 35 (27.2%) and 31 (24%) cases were classified as budding 1, budding 2, and budding 3, respectively. As for PDC, 73 (56.6%), 33 (25.6%) and 23 (17.8%) cases were classified as grade 1, grade 2 and grade 3, respectively. High TB and PDC grades were significantly associated with lymphovascular invasion (p<0.05), nodal metastasis (p<0.05) and high pTNM stage (p< 0.05). For HER2, 5 (3.9%) cases were positive for HER2 expression by IHC (scores 3+), equivocal 9 (7.0%) and negative 115 (89.1%). All HER2 2+ and 3+ (total 14 cases) was further evaluated by FISH analysis and HER2 gene amplification was seen in 4 cases. There is an association between HER2 protein expression status and pTNM stage (p<0.005). Otherwise, there is no correlation between HER2 protein expression with lymphovascular invasion, nodal metastasis, tumour grade, tumour budding or poorly differentiated clusters. Conclusion: There is strong evidence to suggest that tumour budding, and poorly differentiated clusters are an adverse prognostic factor. Our findings indicate that HER2 overexpression occurs in a small population of CRC cases and may benefit with HER2 targeted therapy.